Trying To Bridge the Divide: A Phenomenological Footnote Regarding the Dichotomy Between Empathy and Reasoning - Weber, Barbara; Asgari, Mahboubeh (Philosophical Inquiry in Education, 2021)
In this paper, we discuss the historical relationship between empathy and reasoning from a historical and philosophical (continental and Western philosophy) point of view. We explain how empathy has lost its original aesthetic connotations through its journey from one language and culture to another. Nowadays, we often find a quite reduced understanding of empathy in psychology or education. Following this historical overview and opening up the notion of empathy to its aesthetic origins, we then apply a phenomenological lens and argue that reasoning and perspective-taking are interrelated with empathy, if we understand the importance of human embodiment: We argue that any reasonable argument relies on the fact that we indwell the world through a similar body. It is within this nexus of similarity and difference of embodiment and perceptions that our experiences can interlace. With this argument, we are hoping to address the distrust towards empathy as well as break open simplified conceptualizations of empathy in education towards a more complex understanding of this phenomenon.